Short Documentary Film Implementation at Al Ikhsan Beji Islamic Boarding School as a Media to Improve English Speaking in the Midst of the American Popular Culture Hegemony - Ade Christanty Yudha Bestari; Meilina Haris Mayekti; Dinar Faiza (Pusat Studi Bahasa dan Publikasi Ilmiah, 2020)
Today, the hegemony of American popular culture products is increasingly endemic throughout the world. Therefore, students who in fact live in Islamic boarding schools are expected to be able to use the popular culture, especially YouTube, positively. So that it can be useful for himself and others. This short documentary will be applied at Islamic Boarding School and the results will be published via YouTube. The purpose of this study was to apply the making of a short documentary film at Islamic boarding school as a media for English-language expression. As well as its influence on English Speaking. This research uses a qualitative approach using the method of